Could Ambroxol reduce cytokines in hepatic ischemia-reperfusion injury in rats - ÇETİNEL, ŞULE (My University, 2022)
OBJECTIVES: The aim of the study is to examine the effect of Ambroxol on TNF-α and IL-1β released after liver ischemia-reperfusion injury. BACKGROUND: Many drugs are being tried to reduce ischemia-reperfusion injury, which is life threating problem after many liver surgeries. In this study, it was investigated whether Ambroxol reduces the release of pro-infl ammatory cytokines released after liver ischemia-reperfusion injury. METHODS: Twenty-four Wistar albino rats were divided into 3 groups as Control (CTR; n=8), hepatic ischemia reperfusion (H-IR; n=8) and hepatic ischemia reperfusion+Ambroxol (H-IR+AMB; n=8). In H-IR+AMB group, Ambroxol (30 mg/kg) was administered orally 30 minutes before ischemia period. In H-IR and H-IR+AMB groups underwent 45 minutes of hepatic ischemia followed by a 60-minute reperfusion period. After reperfusion period, tissue and blood samples were collected from euthanised animals. ALT, AST, ALP, LDH, TNF-α, IL-1β concentrations and liver tissues were evaluated. RESULTS: Serum ALT, ALP, AST, LDH, TNF-α and IL-1β values were lower in the H-IR+AMB group compared to the H-IR group. In the histopathological examination, hepatocyte degeneration and congestion in the H-IR group were higher than in the H-IR+AMB group.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Ambroxol; hepatic ischemia reperfusion; pro-inflammatory cytokines; rat; ALPHA-LIPOIC ACID; ISCHEMIA/REPERFUSION INJURY; ANTIOXIDANT; PROTECTS; BIOLOGY; Ambroxol; hepatic ischemia reperfusion; pro-infl ammatory cytokines; rat